ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA PERIODE 2015-2019 - DEA FITRIA KARTIKASARI; SYAFRIONT (AKADEMIKA, 2021)
The purpose of this report is to disclose the results of research aimed at finding out whether there is a significant difference in the financial performance of the company before and after the IPO (Initial Public Offering) of companies listed on the Indonesia Stock Exchange for the period 2015-2019. The population of this research is non-financial companies listed on the Indonesia Stock Exchange with the following criteria: 1) non-financial companies that conducted Initial Public Offering (IPO) in 2018, 2) Availability of financial reports for the two financial years prior to (2015-2016) and two financial years after (2018-2019) conducting an Initial Public Offering (IPO) or financial reports for 2015-2019. The analytical technique method used in this research is a quantitative method through the Non-Parametric Test (Wilcoxon Sign Test). The results showed that there was a significant difference in Current Ratio (CR) between before and after conducting an IPO. There is a significant difference in Debt to Equity Ratio (DER) between before and after conducting an IPO. There is a significant difference in Debt Ratio (DR) between before and after conducting an IPO. There is no significant difference in Net Profit Margin (NPM) between before and after conducting the IPO